INOVASI KURIKULUM PEMBELAJARAN IPAS BERBASIS PROYEK TERINTEGRASI CULTURALLY RESPONSIVE TEACHING UNTUK SISWA SEKOLAH DASAR - Siti Raihan; Amir Pada; Andi Makassau; Nur Abidah Idrus; Andi Dewi Riang Tati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
IPAS (Science and Social Studies) learning in elementary schools still faces challenges, including low student engagement and a lack of integration of local cultural values in learning. This study aims to develop a project-based IPAS learning device integrated with Culturally Responsive Teaching (CRT) for fifth-grade elementary school students in Makassar City. The study employed the 4D development model (Define, Design, Develop, Disseminate), which includes needs analysis, instructional design, product development, and limited trials. The trial was conducted in two elementary schools, involving two teachers and 62 students. Data were collected through learning activity observations, expert validation (material and media), student and teacher questionnaires, and learning outcome tests. Validation by two material experts and two media experts showed the product to be in the "highly valid" category. Observation results indicated strong student engagement (88%), especially in group discussions and project presentations. Student responses revealed high enthusiasm for the culturally contextual and enjoyable learning process. Teachers stated that the learning device was easy to use, systematic, and relevant to students' real-life experiences. Test results showed an increase in average scores from 61.9 (pre-test) to 85.5 (post-test), with a gain score of 0.61 (high category). The project-based learning integrated with CRT effectively enhanced students’ engagement and understanding of IPAS concepts linked to local culture. This learning device is recommended for implementation in multicultural elementary school contexts.